Geopolitical problems in the two parts of Sudan (Journal of the College of Basic Education, 2022)
Despite the secession of southern Sudan, this did not put an end to the problems of Sudan. On the contrary, it exacerbated the problems, not only for both of them, but also for the neighboring Arab-African countries, which are linked with Sudan by overlapping borders, in addition to the tribal overlap with some of them, not to mention that the Some of the movements and nationalities present in those countries are also calling for secession, similar to the state of the South, which leads to the creation of a state of political instability, which in turn will be reflected in the relationship of the two parts of Sudan with the neighboring Arab-African countries.